The Tomás G. Zoebisch collection asociated to Centro de Estudios en Zoología, University of Guadalajara - González-Hernández, Ana Laura; Navarrete-Heredia, José Luis (Instituto de Ecología, A.C., 2011)
We provide an overview of the Entomological Collection Tomas G. Zoebisch, recently donated to the Entomological Collection of the Centro de Estudios en Zoologia, Universidad de Guadalajara.This collection contains 3,790 specimens: 2,952 from Mexico and 838 from other countries. They belong to 31 families and 436 species. Scarabaeidae is the most abundant family (2,601 specimens), followed by Carabidae (684), whereas Pleocomidae and Ochodaeidae are represented by only one specimen each one. Most of the specimens from Mexico were collected in Morelos State. Beetles from other countries are well represented from Peru, Spain and, the United States of America. Labels information was included in two databases: one for Mexican beetles and another one for those of other countries. Copies of these databases are deposited at the Comision Nacional para el Conocimiento y Uso de la Biodiversidad and in the Centro de Estudios en Zoologia.